Power and organization life cycles - (:unkn) unknown (My University, 2015)
A Summary of Henry Mintzberg’s Work on Power and Organizational Life Cycles (Academy of Management Review. 1984. Vol. 9, No. 2. 207‐224)
Keywords: Leadership; Power